A retrospective study on factors influencing pregnancy rate following embryo transfer in cows - M, MUTHA RAO; Y, UMA MAHESH; K, BABU RAO (The Indian Journal of Animal Reproduction, 2023)
_ The aii:11 of the pre~ent stud~ '"'.as to analyze the factors affecting pregnancy rate following non-surgical EmbryoTran_st~r (ET) m cows. ~at1ve (Bos md1cus) Ongole cows super stimulated during mid luteal phase were subjected to nonsurg1c?•embryo collect1on on day 7 of super estrus and embryos were evaluated based on stage of development and qualityTransfer of 3? embryos resulted in an average pregnancy rate of 56.8 %. It was observed that, irrespective of developmentaistage o~ q~ahty of embryo, pregnancy rates were not compromised when recipients were in estrus ± 24 hrs of donor. Theresults md1cate that transfer grade, site of embryo deposition and quality of recipient have profound influence on conceptionrate.
Keywords: Pregnancy; Ongole; embryo transfer